2009
DOI: 10.1515/bc.2009.090
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional aspects of the multidrug efflux pump AcrB

Abstract: The tripartite efflux system AcrA/AcrB/TolC is the main pump in Escherichia coli for the efflux of multiple antibiotics, dyes, bile salts and detergents. The inner membrane component AcrB is central to substrate recognition and energy transduction and acts as a proton/ drug antiporter. Recent structural studies show that homotrimeric AcrB can adopt different monomer conformations representing consecutive states in an allosteric functional rotation transport cycle. The conformational changes create an alternate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 75 publications
(97 reference statements)
1
46
0
Order By: Relevance
“…These genes are part of the acid resistance systems (18). Expression of a pH-inducible protein involved in the stress response (inaA), the major oxygen-insensitive nitroreductase (nfsAB), and the multidrug efflux transporters (acrAB and mdtG) (19) was significantly induced in tetracyclineand enrofloxacin-resistant cells. The regulator of acrAB, acrR, was upregulated 5.9 times in enrofloxacin-resistant cells, resulting in a very comparable upregulation of acrA by a factor of 7.9 and acrB by a factor of 5.8.…”
Section: Resultsmentioning
confidence: 99%
“…These genes are part of the acid resistance systems (18). Expression of a pH-inducible protein involved in the stress response (inaA), the major oxygen-insensitive nitroreductase (nfsAB), and the multidrug efflux transporters (acrAB and mdtG) (19) was significantly induced in tetracyclineand enrofloxacin-resistant cells. The regulator of acrAB, acrR, was upregulated 5.9 times in enrofloxacin-resistant cells, resulting in a very comparable upregulation of acrA by a factor of 7.9 and acrB by a factor of 5.8.…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of restoration depends on the respective affinities of the transported drugs and the tested compound for affinity/ binding sites located inside the efflux pump system. These sites have been proposed from the co-crystallographic analyses (Yu et al, 2003(Yu et al, , 2005 and modelling studies carried out on the AcrB pump (Eicher et al, 2009;Li & Nikaido, 2009;Murakami, 2008;Nikaido & Takatsuka, 2009;Pos, 2009;Takatsuka et al, 2010). Consequently, as the concentration of the compound is increased, competition for these internal binding sites (Nagano & Nikaido, 2009) favours the compound, depending on the respective affinity constant ratio, thereby promoting the intrabacterial retention of the antibiotic.…”
Section: Discussionmentioning
confidence: 99%
“…Data predominantly from crystallization and computer modeling studies have suggested a vestibule and a cleft entrance. The vestibule channel appears to be opened to the so-called "groove" between TM8 and TM9 and is thought to trap substrates from the outer leaflet of the inner membrane, whereas the cleft pathway is thought to allow the entrance of substrates from the periplasm between subdomains PC1 and PC2 further apart from the upper ending of the TM domain (9,(12)(13)(14)(20)(21)(22). A third option, an entrance on the back side of AcrB open to the central cavity built from the intermolecular space between the protomers is considered to be less likely (13,21).…”
mentioning
confidence: 99%